Accelerated Confined Mass Transfer of MoS2 1D Nanotube in Photo‐Assisted Metal–Air Batteries - Liang, Shuang; Zheng, Li‐Jun; Song, Li‐Na; Wang, Xiao‐Xue; Tu, Wen‐Bin; Xu, Ji‐Jing (Advanced materials (Weinheim), 2024)
Applying solar energy into energy storage battery systems is challenging in achieving green and sustainable development, however, the efficient progress of photo‐assisted metal–air batteries is restricted by the rapid recombination of photogenerated electrons and holes upon the photocathode. Herein, a 1D‐ordered MoS2 nanotube (MoS2‐ONT) with confined mass transfer can be used to extend the lifetime of photogenerated carriers, which is capable of overcoming the challenge of rapid recombination of electron and holes. The tubular confined space cannot only promote the orderly separation and migration of charge carriers but also realize the accumulation of charge and the rapid activation of oxygen molecules. The concave surface of MoS2‐ONT can improve the carrier separation ability and prolong the carrier lifetime. Meanwhile, the ordered tubular confined space can effectively realize the rapid transfer of charge, ion, and oxygen. Under light irradiation, a fast oxygen reduction reaction kinetics of 70 mW cm−2 for photo‐assisted Zn–air battery is achieved, which is the highest value reported for photo‐assisted Zn–air batteries. Significantly, the photo‐assisted Li–O2 battery based on MoS2‐ONT also shows superior rate capability and other exciting battery performance. This work shows the universality of the confined carrier separation strategy in photo‐assisted metal–air batteries. Benefiting from the high photogenerated electron–hole separation efficiency and the inherent mass transfer characteristics of MoS2 confined nanotubes, the photo‐assisted Zn–air battery delivers a high power density (70 mW cm−2), and obtains a Li–O2 battery with excellent rate performance, which fully proves the universality of this confined structure to achieve simple, efficient and fast photogenerated carrier separation dynamics.